Gimbal control of an airborne Pan-Tilt-Zoom camera for visual search - Chacón Ríos, Natalia R.; Mondal, Sabyasachi; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2025)
This paper presents the development of an optimized visual search algorithm for unmanned aerial vehicle (UAV) equipped with Pan-Tilt-Zoom cameras, designed to account for platform dynamics and disturbances. The study involves the design and evaluation of various gimbal control strategies to stabilize the camera’s orientation, ensuring effective area coverage despite UAV attitude changes. A comparative analysis of control methods, including Proportional–integral–derivative (PID), Disturbance Observer (DOB), Iterative Learning Control, Internal Model Control, Active Disturbance Rejection Control, and their combinations, highlights the importance of advanced controllers in maintaining camera stability under complex conditions such as coriolis, centripetal, and gyroscopic disturbances. The combination of PID and DOB provided superior disturbance rejection, making it a suitable choice for challenging flight scenarios. Additionally, an optimized coverage path planning algorithm was developed to maximize image coverage while minimizing flight time, turns, and overlap, taking into account field of view, resolution, and terrain constraints. Simulation results demonstrate the effectiveness of this approach, achieving full area coverage with enhanced efficiency. The framework developed in this study provides a solid foundation for reliable and precise UAV-based search operations, particularly in dynamic and complex environments.